Synthesis and Biological Activity of Divalent Metal Chelates of Metronidazole - Kesharwani, Rachna; Singh, Pramila (Asian Journal of Chemistry, 2010)
The complexing behaviour of metronidazole (1H-imidazole-1-ethanol- 2-methyl-5-nitro) towards Co(II), Ni(II), and Cu(II) has been studied. The complexes of the general formula ML2X2·2H2O and CuL4Cl2 [where M = Co(II) or Ni(II)], L = C6H9N3O3 (drug) as ligand) and X = Cl- ] have been prepared and characterised by elemental analysis, molar conductance, magnetic susceptibility measurements, electronic and infrared spectral data. They have also been tested for their antibacterial activities.